Contribuição diferencial de quatro famílias de aves dispersoras de sementes na recuperação de habitats florestais - Gonzalez, Susana Pires [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
A rápida perda de diversidade biológica nos trópicos através da fragmentação de habitats pode ser revertida com o uso de técnicas de nucleação. Nesse sentido, um dos processos de facilitação é o uso de poleiros naturais e artificiais. Este se beneficia da natureza potencialmente dispersora de aves frugívoras. No presente estudo foram testadas as seguintes hipóteses: 1) famílias de aves menos dependentes de habitats florestais e com maior amplitude de itens alimentares (Turdidae e Tyrannidae) são mais eficientes na dispersão de sementes sob poleiros localizados em áreas degradadas; 2) famílias de aves que ocupam preferencialmente o interior de florestas e cuja dieta é composta principalmente por frutos (Ramphastidae e Pipridae) são mais eficientes na manutenção de remanescentes florestais. Esta pesquisa foi executada por meio de extensa revisão bibliográfica com área de abrangência exclusiva em território brasileiro. Comparou-se a contribuição potencial de quatro famílias que consomem frutos para a dispersão de sementes. O foco do estudo foram suas características de uso de hábitat e dieta. Concluiu-se que houve dicotomia entre famílias frugívoras especialistas e generalistas, quanto às suas características como dispersoras de sementes. Ramphastidae e Pipridae, classificados como essencialmente frugívoros, tiveram maior ocupação de ambientes florestais, menor flexibilidade na ocupação de habitats e estratos florestais, maior sensibilidade a alterações antrópicas, atuando basicamente na manutenção de ambientes florestais. Já as famílias generalistas Turdidae e Tyrannidae, com menor sensibilidade a alterações antrópicas, ocupação de ambientes com diversos graus de cobertura vegetal e estratos...

The rapid loss of biological diversity on the tropics through habitat fragmentation can be reverted using nucleation techniques. In this regard, one of the facilitation processes is the use of natural and artificial pearches. This technique takes advantage of the potential seed dispersal nature of frugivorous birds. In the present study the following hypotheses have been tested: 1) families of birds less dependent of forest habitats and with more amplitude of food items (Turdidae and Tyrannidae) are more efficient spreading seeds by the pearchs located in degraded areas; 2) Birds that preferably occupy the interior of forests and whose diet is mainly compounded by fruits (Ramphastidae and Pipridae) are more efficient on the maintenance of forest remnants. This research was produced by means of extensive bibliographic review, regarding the Brazilian territory as the study`s coverage area. The potential contribution of four families that consume fruits causing the dispersal 3 of seeds has been comparatively analyzed. The focus of this study was mainly their characteristics of usage of the habitat and diet. In conclusion, it was noticed a dichotomy among specialized and generalist frugivorous families regarding their characteristics as seed spreaders. Ramphastidae and Pipridae, classified as essentially frugivorous, had wider occupation of forestal environments, narrower flexibility on the occupation of habitats and forestal stratum, bigger sensibility to anthropic change, basically acting on the maintenance of forestal environments. On the other hand, the generalist families Turdidae and Tyrannidae, with lower sensibility to anthropic changes, environment occupation with diverse degrees of plant coverage and strata, including degraded areas. Turdidae and Tyrannidae are also the main occupiers of natural and artificial... (Complete abstract click electronic access below)
Keywords: Ecologia animal; Ave; Ecossistemas; Ecologia florestal; Seed dispersal; Ornitochory